2005
DOI: 10.1016/s1359-835x(04)00167-8
|View full text |Cite
|
Sign up to set email alerts
|

Folding of woven composite structures

Abstract: This paper investigates one-ply and two-ply laminates made from woven T300 carbon fibre and Hexcel 913 and 914 epoxy resins. These laminates are of interest for deployable structure applications. The maximum surface bending strain, measured by means of a large-displacement buckling test, is found to be 2.8% for one-ply and 1.9% to 2.2% for two-ply specimens in the direction of the fibres. In tension the maximum strains in the fibre direction are 0.9% to 1.0% and in compression 0.4% to 1.0%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Of course, the peak bending strains are compared with the ultimate strains for fibers. However, numerous experiments on thin laminates made from woven CFRP composites [4,5] have shown that these laminates are able to survive peak bending strains that are much larger than those obtained from the above approach. Therefore, here it will be assumed that a woven lamina in bending fails when the strain at the center of the outermost yarn reaches the ultimate value:…”
Section: Minimum Bend Radius R Minmentioning
confidence: 99%
“…Of course, the peak bending strains are compared with the ultimate strains for fibers. However, numerous experiments on thin laminates made from woven CFRP composites [4,5] have shown that these laminates are able to survive peak bending strains that are much larger than those obtained from the above approach. Therefore, here it will be assumed that a woven lamina in bending fails when the strain at the center of the outermost yarn reaches the ultimate value:…”
Section: Minimum Bend Radius R Minmentioning
confidence: 99%